2015
DOI: 10.1128/mcb.00248-15
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Role of the C-Terminal Tail in the Regulation of the Epidermal Growth Factor Receptor

Abstract: The ϳ230-residue C-terminal tail of the epidermal growth factor receptor (EGFR) is phosphorylated upon activation. We examined whether this phosphorylation is affected by deletions within the tail and whether the two tails in the asymmetric active EGFR dimer are phosphorylated differently. We monitored autophosphorylation in cells using flow cytometry and found that the first ϳ80 residues of the tail are inhibitory, as demonstrated previously. The entire ϳ80-residue span is important for autoinhibition and nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
102
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(114 citation statements)
references
References 50 publications
11
102
0
1
Order By: Relevance
“…Because EGFR is the only active kinase in this complex, the resulting receptor phosphorylation is a result of its activity. Although phosphorylation of EGFR in cis in the active dimer has been shown to be less pronounced than in trans, it does occur (36). Why then cannot EGFR autophosphorylate itself when stimulated with NRG in the presence of HER3?…”
Section: Resultsmentioning
confidence: 99%
“…Because EGFR is the only active kinase in this complex, the resulting receptor phosphorylation is a result of its activity. Although phosphorylation of EGFR in cis in the active dimer has been shown to be less pronounced than in trans, it does occur (36). Why then cannot EGFR autophosphorylate itself when stimulated with NRG in the presence of HER3?…”
Section: Resultsmentioning
confidence: 99%
“…The intrinsically disordered properties of these CTTs also explain why these regions are mostly absent from crystallographic studies on EGFR (7,55). Portions of the EGFR tail located close to the kinase domain have been shown to be responsible for EGFR autoinhibition (56).…”
Section: Discussionmentioning
confidence: 99%
“…The deletion of residues 982-1054 in the EGFR vIVb mutant is of particular importance in downstream signaling and kinase activation and has been shown to promote tumor formation. This region has been characterized via crystallography as containing an AP2-helix and other secondary structure elements, which appear to interact with the kinase domain in a manner that inhibits activation (4,55,56). In a study by Kovacs et al (55), serial deletions of tail regions revealed specific regions important for autoinhibition as they relate to the oncogenic vIVb mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Another important issue regarding mTOR signal activation in TMZ-R U87 cells is genetic alteration of the mTOR gene (29)(30)(31). Briefly, three studies regarding mTOR mutation research have been cited.…”
Section: Inhibitory Effect Of Stx-0119 And/or Rapamycin On In Vivo mentioning
confidence: 99%
“…Interestingly, a novel mutation (E1004K) located in the C-terminal tail domain of EGFR was found in Table I. Considering that the N-terminal half of the EGFR C-terminal tail domain has an inhibitory function in EGFR signal activation (31) and that a neighboring mutation (ER1005-1006KD) was reported to induce spontaneous activation of EGFR phosphorylation (17), this mutation (E1004K) might be involved in EGFR signaling. Alternatively, a novel somatic mutation of the YKL-40 gene (G292R) was also found, but it likely dose not function in signal transduction.…”
Section: Inhibitory Effect Of Stx-0119 And/or Rapamycin On In Vivo mentioning
confidence: 99%